Dental age estimation methods tested in Pakistani Population – A scoping review of cross-sectional studies - Khan, Amber; Yaqoob, Bakhtawar; Franco, Ademir (Acta Odontologica Indonesia, 2026)
Background: Forensic dentistry is still a growing field in Pakistan. The lack of scientific evidence on the subject can lead to difficulties in situations where age assessment plays a significant role in areas such as criminal and civil proceedings. In large-scale disasters such as earthquakes and accidents, correct investigation of chronological age is less difficult if there is evidence for a specific group of people. Objectives: The purpose of this scoping review was to screen the scientific literature and to find the studies that have been performed with different age estimation methods that have been applied to the Pakistani population over the years. Methodology: It was carried out in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA-ScR) guidelines by searching the following online databases: PubMed/Medline, Scielo,Lilacs,Sciencedirect,Open grey Base, and OATD. A total of 1771 articles were found out. Results: A total of 17 studies remained for full text reading. Out of the 17 studies, eight were excluded because of their study design and two were out of topic. One study was added by expert opinion and a total of eight articles were included in this scoping review including Demirjian’s method, Nolla, Willem’s, Kohler’s, Bang and Ramm, Cameriere,Lamendin’s and Kvaal’s method. Conclusion: The clinical implications of this study are relevant to forensic odontology and clinical dentistry. Overestimation and underestimation of dental age using different methods determines the difference between chronological age time and estimated dental age.